Surgical management of a child suffering from osteogenesis imperfecta, treated with bisphosphonates - a case report - Lipczyńska-Lewandowska, Małgorzata; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article presents a case of surgical extraction of impacted third molars in a 17 y. o. boy with osteogenesis imperfecta.